Use of hand hydraulic dynamometers as an overall evaluation of the upper-limb weakness in patients with thoracic outlet syndrome - Fouasson-Chailloux, Alban; Daley, Pauline; Menu, Pierre; Gadbled, Guillaume; Bouju, Yves; Gautier, Giovanni; Pomares, Germain; Dauty, Marc (Frontiers in Neurology, 2022)
Patients with neurogenic thoracic outlet syndrome report pain and upper-limb weakness. They complain about weakness occurring on the entire upper-limb, especially at the hand and the shoulder levels. Hydraulic dynamometers can reliably assess the strength of the hand, and isokinetic shoulder testing can provide accurate and reliable evaluations of the rotators strength. Yet, isokinetic proximal assessment needs expensive tools, whereas hydraulic hand dynamometers are cheap and easy to use. We aimed to assess the correlation between the isokinetic shoulder strength and the hand grip and the key pinch strength. The grip strength was evaluated with a hydraulic hand dynamometer and the key pinch with a pinch gauge. Isokinetic rotators strength tests were performed using a Humac Norm® dynamometer at 60 and 180°/s. One-hundred and thirty patients had been included, 72% of women, mean age of 39.8 ± 9.5. Symptomatic hands presented a strength deficit of 12.2% on the grip (p<0.0001) and 10% on the key pinch (p=0.01). Isokinetic strength was lower on the symptomatic shoulders at 60 and 180°/s concerning medial rotators (-10.3% and -8.8%, respectively (p=0.02)) and lateral rotators (-10.8% and -10%, respectively (p=0.04 and p=0.03)). There was a moderate correlation between the grip strength of the symptomatic upper-limbs and the isokinetic rotators strength (p < 0.001). The key pinch strength was moderately correlated to the isokinetic medial and lateral rotators strength at 60°/s (p < 0.001). Hand dynamometers could prove useful during medical consultations or in outpatient management to assess upper-limb overall weakness, but isokinetic measurement remains the gold standard for a precise evaluation.